Africa Soil Health Consortium: Handbook For Integrated Soil Fertility Management - Fairhurst, T. (CABI, 2013)
This handbook presents Integrated Soil Fertility Management, commonly known as ISFM, as a key contributor to improving Africa's soil and crop productivity, especially for the key staples in the continent that include maize, legumes, rice, cassava, bananas, sorghum, millet and coffee. It is meant for training of extension workers on soil fertility management techniques in sub-Saharan Africa and for workers involved in rural development that would like to learn more about the principles of ISFM. The handbook is also a useful primer on ISFM for educational organizations such as universities and technical colleges, and organizations involved in the development of policy on agriculture and rural development that need reference materials on ISFM techniques. Produced by the Africa Soil Health Consortium (ASHC), this handbook is part of a series of materials and publications on ISFM produced for stakeholders including extension personnel, smallholder farmers, agro-dealers, policy makers and training institutions. Other materials include cropping and plant nutrition guides, policy briefs, training manuals and practical information for extension workers and farmers. See the ASHC website for further details. The ASHC works with initiatives in sub-Saharan Africa to encourage the uptake of ISFM practices. ASHC is coordinated by CABI in partnership with international and national science and agriculture organizations with support from the Bill & Melinda Gates Foundation.